Effect of using brain-based learning theory in motivation to 4th year female students in Jordan - Al-Shaweesh, Juman Ghalib (Journal of Curriculum and Teaching Methodology, 2022)
This research aimed to know the effect of using brain-based learning theory on motivation to 4th year female students in science. The sample consists of (50) female students and they were in random allocation to two groups equally each of them of (25) female students from the experimental group which learnt according to ordinary method The research himself taught the two groups, and he made motivation scale consisted of (29) The results showed the excellence of the experimental group to the controlling group in motivation scale The researcher submitted a number of recommendation and suggestions.